2022
DOI: 10.22207/jpam.16.3.28
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: Lactic Acid Bacteria have Antibacterial Activity and Downregulate Biofilm Genes of Uropathogenic E. coli

Abstract: Urinary tract infections (UTIs) are regarded as one of the most serious infections worldwide. Uro Pathogenic E. coli (UPEC) accounts for nearly 80% of UTI infections in females. This study investigated the antibacterial and antibiofilm effects of Lactobacillus acidophilus (l. acidophilus) and Lactobacillus plantarum (lb. plantarum) on multidrug-resistant E. coli obtained from urine samples. Complete bacteriological identification was conducted on 45 E. coli isolated from 80 urine samples of females with UTIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additionally, all isolates were urease negative except Klebsiella pneumoniae which was positive. Dawwam et al (2022) confirmed biochemical tests of E. coli that gave methyl red and indole positive, urease and citrate negative.…”
Section: Multiple-tube Fermentation Techniquementioning
confidence: 62%
“…Additionally, all isolates were urease negative except Klebsiella pneumoniae which was positive. Dawwam et al (2022) confirmed biochemical tests of E. coli that gave methyl red and indole positive, urease and citrate negative.…”
Section: Multiple-tube Fermentation Techniquementioning
confidence: 62%
“…They play a significant role in maintaining the homeostasis of this environment and the disturbance of which could affect the development of many uropathogens 15 , 39 . Many recent studies focus on the antibacterial and antibiofilm properties of natural microbiota of the urinary tract against the most common UTI pathogens such as: Escherichia coli, which cause approximately 80% of UTIs 40 , 41 , Proteus mirabilis 14 , 42 or Klebsiella pneumoniae 43 , 44 . Additionally, a lot of scientific works concentrate on the practical use of selected Lactobacillus strains to UTIs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…plantarum and L. acidophilus strains reduced the ability of uropathogenic E. coli (UPEC) to develop biofilms by 39.63% and 56.3%, respectively. The variations in the gene expressions of csgA , crl , and csgD were significantly downregulated after separate treatment with L. plantarum and L. acidophilus suspensions [ 79 ]. Hossain et al examined the effect of four sub-MICs of L. plantarum M.2 and L. curvatus B.67 (1/2, 1/4, 1/8, and 1/16 MIC) on the formation of L. monocytogenes biofilm on various food contact surfaces.…”
Section: Anti-virulence Treatment Strategiesmentioning
confidence: 99%